Nonlinear bending and snap-through instability analyses of conical shell panels using element free Galerkin method. (January 2018) - Watts, Gaurav; Singha, M.K.; Pradyumna, S.
Abstract: The nonlinear bending and snap-though instability phenomenon of isotropic and composite conical shell panels are investigated here using the element free Galerkin (EFG) method with moving kriging (MK) shape function. Sanders' shell theory along with von Kármán strain-displacement assumptions are employed to derive the nonlinear equations of equilibrium, which are solved by modified Riks technique in conjunction with Newton-Raphson method. The convergence and accuracy of the EFG method are examined for the linear and nonlinear bending behavior of conical shell panels. Thereafter, the effect of geometrical parameters on the nonlinear stability characteristics of conical panels is investigated under different loading conditions. New results for linear as well as nonlinear bending behavior of isotropic and laminated conical shell panels, hitherto not found in the literature, are presented for future reference. Highlights: Element free Galerkin method with moving kriging shape function is used to analyze conical panels. Sanders' shell theory and von Kármán strain-displacement assumption are used in the analysis. Un-symmetric conical panels exhibit multiple snap-through and snap-back phenomenon.